Hubungan Pengetahuan Nilai Guna Rekam Medis Dengan Perilaku Pengisian Rekam Medis oleh Perawat di Rumah Sakit Santa Elisabeth Medan - Pestaria Saragih; Arjuna Ginting; Beatrice Rosita Lumbanraja (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Use value of medical records is an aspect contained in the use of medical records. The behavior of filling out a medical record is a person's action in filling out a complete medical record. The medical record is filled in completely so that the information presented is in accordance with what is in the medical record. One way to improve the behavior of filling out medical records so that they are complete is to increase knowledge of the use value of medical records. The aim of the study was to analyze the relationship between knowledge of the use value of medical records and the behavior of filling out medical records by nurses at Elisabeth Hospital. The research method used is analytic research using a cross-sectional design. Statistical test using chi-square test. The research population of inpatient nurses was 150 nurses and the research sample was 58 respondents. The results of the study showed that 35 people (60.3%) had knowledge in the high category, 30 people (51.7%) filled out medical record behavior in the good category. The results of the Chis-square test obtained a p-value of 0.002 (p <0.05) indicating that there is a significant relationship between knowledge of the use value of medical records and the behavior of filling out medical records. It is hoped that from the results obtained by medical workers at Santa Elisabeth Hospital Medan that knowledge can be increased again so that the behavior of filling out medical records in terms of medical record completeness can be even better